Developing the Knowledge Management System Framework in National Company: A Case Study of XYZ Company in Indonesia - Nurdin, Ali; Lubis, Muharman; Abdullah Muhammad, Hasan; Naufal Wirawan, Muhammad; Addini Firdaus, Fitri (Acceleration, Quantum, Information Technology and Algorithm Journal, 2024)
The Knowledge Management Application facilitates a medium for knowledge exchange, Its skills facilitate the acquisition of individuals' experiences and knowledge. Knowledge management tools are essential in large corporations, especially in enterprise organizations (private companies), in facilitating the retention and effective communication of pertinent information among staff members. Private enterprises often own substantial data and information in perpetually updatable formats that can be effectively leveraged to enhance the organization's knowledge and operational operations. Nevertheless, recent studies have revealed that knowledge management (KM) is still in its nascent phase for most private enterprises in Indonesia. The performed work investigated the existing Key Management Activities in a private company in Indonesia, with a specific focus on XYZ Company as the case study. Ac-cording to the evaluation, XYZ Company has not yet started constructing a specific Knowledge Management System (KMS), despite putting significant effort into developing core application systems to cover important business activities. Thus, the work introduces the structure for the growth of KMA in the organization.